INTERNALIZATION OF ISLAMIC MODERATION VALUES IN PAI LEARNING AT SMA MA'ARIF NU 1 BANYUMAS - Muhammad Misbah; Ikhsan Nur Fahmi (Al-Qalam, 2021)
Schools are one of the right places to spread the sensitivity of students on a different variety. SMA Ma'arif NU 1 Banyuma, as an educational institution, is able to internalize the Islamic moderation values of students through various activities in the school. This research aims to uncover and analyze the internalization of Islamic moderation values in the study of Islamic Religious Education (PAI) at SMA Ma'arif NU 1 Banyumas. The type of research is field research. Data mining was obtained through interviews with informants. The observation was conducted to see PAI learning activities and education in and out of the classroom, as well as PAI learning documentation. Data triangulation was used for the validation of the obtained data. Data analysis techniques were through three steps; data reduction, data display, and conclusion drawing. The results of this study are the values of Islamic moderation internalized in PAI learning are the values of al-'adālah, tawāzun, tasāmuḥ. The internalization process is carried out through transformational value, transactional value, and trans- internalization value. The strategies used are introduction, habituation, civility, and practice. The implications show that students are used to performing worship, respecting teachers and friends, social caring, being tolerant, being discipline, being environmentally responsible, and obeying the rules.